MADRASAH HEAD MANAGEMENT IN IMPROVING TEACHER PERFORMANCE AT MIN 4 LANGKAT DISTRICT - Sartika Hutasuhut; Neliwati Neliwati; Khairuddin Khairuddin (Research and Development Journal of Education, 2023)
The duties of a madrasah headmaster include managing the improvement of teacher performance in the madrasah. To lead effectively, the headmaster must design a well-planned work program. MIN 4, as an educational institution, certainly requires professional staff members who demonstrate good performance in advancing the madrasah. This research utilizes qualitative research methods with three data collection techniques: interviews, observations, and documentary studies. The data analysis involves data reduction, data display, and conclusion/verification. The research findings indicate that teachers possess mastery of teaching materials, conduct classroom administration, and perform evaluations. The headmaster has established a plan to enhance teacher performance in MIN 4, Kabupaten Langkat, through the madrasah's vision and mission, as well as the work program outlined in annual and mandatory monthly meetings. The headmaster of MIN 4, Kabupaten Langkat, implements various efforts to improve teacher performance, including providing opportunities for them to participate in training programs such as the Teacher Working Group (KKG) and Subject Teacher Discussion Forum (MGMP), as well as conducting direct supervision of their performance. Teachers are also guided in developing teaching tools, such as syllabi, lesson plans, teaching plans, worksheets, and assessments, as well as creating instructional media. The headmaster conducts routine monitoring of teacher performance to prevent possible negligence in carrying out their duties, by assessing their level of discipline in task execution and responsibility. The goal is to prevent any deviation in teacher performance within the madrasah. The headmaster continues to motivate subordinates to fulfill their tasks and obligations according to predetermined targets, especially regarding discipline in completing classroom administration. Teachers are expected to adhere to all applicable regulations and guidelines in MIN 4, Kabupaten Langkat.